1979
DOI: 10.1073/pnas.76.11.5972
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of active and inactive forms of endorphins in rat pituitary and brain.

Abstract: The recent isolation and identification of a-N-acetyl forms of the C-Fragment of lipotropin (fl-endorphin, residues 61-91) and the C'-Fragment (residues 61-87) [Smyth, D. G., Massey, D. E., Zakarian, S. & Finnie, M. (1979) Nature (London) 279, 252-254] has led to a study of their distribution in the pituitary and brain of the rat. Regions were mapped by the method of immunofluorescent staining and the reactive peptides were determined by immunoassay after extraction, gel filtration, and ion exchange chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(53 citation statements)
references
References 29 publications
4
48
1
Order By: Relevance
“…vated form of 3-EP (4,8). The analgesic and binding potencies of human /-EP- [ph-EP-(1-27)], 2% and 30% relative to human /3-EP (13h-EP) (9,10), make this peptide a good candidate for an inhibitor of l3-EP action.…”
mentioning
confidence: 99%
“…vated form of 3-EP (4,8). The analgesic and binding potencies of human /-EP- [ph-EP-(1-27)], 2% and 30% relative to human /3-EP (13h-EP) (9,10), make this peptide a good candidate for an inhibitor of l3-EP action.…”
mentioning
confidence: 99%
“…Cell-free messenger RNA translation and pulsechase chromatographic studies have shown that a-endorphin (,BEP) and ACTH share a common, 31K dalton precursor in the anterior pituitary (7), neuro-intermediate lobe (8), and hypothalamus (9), although the posttranslational processing of the 31K precursor varies between tissues (10,11). There are some reports that plasma and pituitary immunoreactive (ir)-#EP, like ACTH, may be subject to glucocorticoid feedback inhibition; the area, however, remains one of some controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these peptides occurs also in an a-N-acetyl form (1)(2)(3)(4)(5). Studies of the regional distribution and biosynthetic pathways of the 1-EPrelated peptides in the brain and pituitaries have shown distinctive proportions of these forms in specialized areas arising from differential proteolytic cleavages and acetylation of ,3-EP (6)(7)(8). Of various peptides related to P-EP, only the unmodified hormone possesses potent analgesic properties.…”
mentioning
confidence: 99%